14/#650 The value of PET/CT for cytoreductive surgery selection in recurrent ovarian carcinoma. (4th December 2022) - Nunes, Rafael; Teixeira, Flavio; Goncalves, Bruna; Faloppa, Carlos; Kumagai, Lillian; Mantoan, Henrique; Badiglian-Filho, Levon; Guimaraes, Andrea; Costa, Alexandre Da; Baiocchi, Glauco
Abstract : Objectives: To evaluate the role of PET/CT in predicting no residual disease (NRD) after secondary cytoreductive surgery (SCS) compared to MSK criteria, iMODEL and AGO Score. Methods: We analyzed 122 patients with platinum-sensitive ovarian carcinoma submitted to SCS between July 2008 and December 2021. We excluded patients that did not have PET/CT, without sufficient data and who received chemotherapy before SCS. We ultimately included 69 patients. Results: The median first relapse interval was 23 months (range, 6.05–104.2). Variables that correlated with NRD were PCI [OR 0.91 (0.83–0.99) 95%CI; p=0.044], ECOG0 [OR 8.0 (1.34–47.5) 95%CI; p=0.022] and number of lesions in PET/CT of ≤2 [OR 6.0 (1.24–28.9); 95%CI; p=0.026]. Considering patients with ≤2 lesions on the PET/CT, 92.3% had NRD. We recorded a sensitivity, PPV, NPV and accuracy of 85.7%, 92.3%, 33.3% and 81.2%, respectively. NRD would be achieved after fulfilling MSK criteria, iMODEL and AGO Score in 89.1%, 88.1% and 85.9%, respectively. The accuracy in prediction NRD of MSK criteria, iMODEL and AGO Score was 87%, 83.3% and 77.3%, respectively. PET/CT had a good agreement with AGO Score and iMODEL. The addition of PET/CT to the models increased the NRD rates (MSK+PET/CT, iMODEL+PET/CT and AGO+PET/CT NRDs in 92.2%, 91.8%, and 89.4%, respectively), however impaired their accuracy performance. Conclusions: We found NRD in 92.3% after the presence of ≤2 lesions in PET/CT with an accuracy of 81.2%. PET/CT did not increase the accuracy performance of MSK criteria, iMODEL and AGO Score models.